Synthesis of a Hydrogen Isotope-Labeled SGLT1 C-Glucoside Ligand for Distribution and Metabolic Fate Studies - Giuseppe D’Orazio; Barbara La Ferla (Molbank)
Over the last decades, a novel immunological function was established for the sodium–glucose co-transporter 1 (SGLT1), a protein involved in sugar absorption in the small intestine. High-glucose dosage and pharmacological concentrations of a C-glucoside analog showed a protective role in in vitro and in vivo models of severe inflammation states; experimental evidence suggests the engagement of SGLT1 in these processes. The mechanism of action underlying the protection is still unclear. To enhance our understanding of the molecular mechanisms responsible for this protection, we have developed a synthesis for the preparation of hydrogen isotope-labeled versions of the C-glucoside hit compound. Specifically, we report the synthesis of the deuterium-labeled derivative, which can be utilized for mass spectrometry-based research to examine the compound’s metabolic pathway, distribution, and cellular/tissue localization. The synthetic method developed can be extended to produce the tritiated analog, serving as a radioactive tracer.